2020
DOI: 10.30602/jvk.v6i1.434
|View full text |Cite
|
Sign up to set email alerts
|

Pendampingan Kader Menggunakan Kartu Aksi Gizi Meningkatkan Pola Asuh Ibu

Abstract: AbstrakLatar Belakang. Masalah gizi masih menjadi pusat perhatian di negara berkembang seperti Indonesia. Pada tahun 2030 tujuan utama Sustainable Development Goals (SDGs) adalah mengakhiri segala masalah malnutrisi. Pola asuh ibu balita berdampak pada pertumbuhan dan perkembangan balita. Kondisi ini harus menjadi perhatian khusus, mengingat bahwa kecukupan gizi dari asupan makan sangat berkaitan erat dengan status gizi balita. Penelitian ini bertujuan untuk mengetahui pengaruh pendampingan gizi oleh k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Through SIMPATIK, mothers' knowledge and diversity of food consumption for toddlers increased. This study is in line with the study by Junita et al (2020) showing that nutrition education, accompanied by a nutrition officer, can increase 4,19 points by providing a variety of toddler foods. Before 7,30 ± 0,99 2,18 ± 0,49 0,000 After 9,48 ± 0,95 Diversity of feeding intake Before 2,83 ± 0,95 0,99 ± 0,34 0,000 After 3,82 ± 1,28…”
Section: The Impact Of Simpatik Website Nutrition Education On Knowle...supporting
confidence: 92%
See 1 more Smart Citation
“…Through SIMPATIK, mothers' knowledge and diversity of food consumption for toddlers increased. This study is in line with the study by Junita et al (2020) showing that nutrition education, accompanied by a nutrition officer, can increase 4,19 points by providing a variety of toddler foods. Before 7,30 ± 0,99 2,18 ± 0,49 0,000 After 9,48 ± 0,95 Diversity of feeding intake Before 2,83 ± 0,95 0,99 ± 0,34 0,000 After 3,82 ± 1,28…”
Section: The Impact Of Simpatik Website Nutrition Education On Knowle...supporting
confidence: 92%
“…Studies in Kenya that improve the competence of mothers who need social support are assisted by health workers in the practice of administering complementary foods to toddlers (Schneider et al, 2017). Other studies have shown that nutrition education using nutrition action cards for toddler mothers can increase the variety of toddlers' foods (Junita et al, 2020). Nutrition education carried out by visiting homes can improve the diversity of food consumption among toddlers (Janmohamed et al, 2020) Much research has been conducted on nutrition education to increase the nutritional knowledge of toddler mothers.…”
Section: Abstrakmentioning
confidence: 99%
“…Beberapa penelitian menunjukan edukasi gizi dapat meningkatkan pengetahuan ibu, makanan balita lebih beragam, dan gizi balita membaik 9 . Melalui pelatihan dan pendampingan kepada ibu balita, kader dengan teknik bina suasana dan pendekeatan keluarga mampu meningkatkan pengetahuan ibu balita dalam memberikan makanan pendamping air susu ibu (MP-ASI) dan keragaman konsumsi makanan balita 7,10 Pada zaman digitalisasi akses informasi edukasi gizi mudah didapat untuk menunjang peningkatan pengetahuan kesehatan yang cepat menggunakan website. Penggunaan website dapat memperjelas informasi yang disampaikan karena tampilan lebih menarik, interaktif, dan bisa diakes kapan saja 11,12 Pemberian edukasi gizi melalui media merupakan salah satu cara untuk mempermudah ibu balita dalam memahami materi 13 .…”
Section: Pendahuluanunclassified
“…The success of the program, among others, is influenced by the existence of examples or role models for the community by utilizing the local culture. An example is the success of the PHBS program, thanks to the support of non-formal community role models such as traditional leaders (Junita et al, 2020).…”
mentioning
confidence: 99%